Aberrant imprinting in mouse trophoblast stem cells established from somatic cell nuclear transfer-derived embryos. Issue 7 (3rd July 2018) - Hirose, Michiko; Hada, Masashi; Kamimura, Satoshi; Matoba, Shogo; Honda, Arata; Motomura, Kaori; Ogonuki, Narumi; Shawki, Hossam H.; Inoue, Kimiko; Takahashi, Satoru; Ogura, Atsuo
ABSTRACT: Although phenotypic abnormalities frequently appear in the placenta following somatic cell nuclear transfer (SCNT), mouse trophoblast stem cells (TSCs) established from SCNT embryos reportedly show no distinct abnormalities compared with those derived from normal fertilization. In this study, we reexamined SCNT–TSCs to identify their imprinting statuses. Placenta-specific maternally imprinted genes ( Gab1, Slc38a4, and Sfmbt2 ) consistently showed biallelic expression in SCNT–TSCs, suggesting their loss of imprinting (LOI). The LOI of Gab1 was associated with decreased DNA methylation, and that of Sfmbt2 was associated with decreased DNA methylation and histone H3K27 trimethylation. The maternal allele of the intergenic differentially methylated region (IG–DMR) was aberrantly hypermethylated following SCNT, even though this region was prone to demethylation in TSCs when established in a serum-free chemically defined medium. These findings indicate that the development of cloned embryos is associated with imprinting abnormalities specifically in the trophoblast lineage from its initial stage, which may affect subsequent placental development.